Epidemiological characterization of congenital syphilis in a health region of the northern zone in the state of Ceará, Brazil - David Gomes Araújo Júnior; Maria Adelane Monteiro da Silva; Anna Larissa Moraes Mesquita; Verena Emmanuelle Soares Ferreira; Maria Socorro Carneiro Linhares (Universidade Estadual de Maringá, 2021)
The study sought to investigate the epidemiological profile of congenital syphilis in a health region in the State of Ceará, in the period from 2015 to 2019. This is a descriptive epidemiological study, with a quantitative approach, with secondary data collected through the Health System. Information on Notifiable Diseases and Live Birth Information System. There were a total of 248 cases: 65 cases in 2015, 50 in 2016, 45 in 2017, 51 in 2018 and 37 in 2019. The incidence of congenital syphilis was: 8.1 (2015), 6.1 (2016), 5.1 (2017), 5.3 (2018) and 3.9 (2019). In 62.9% of cases from all the years, women were between 20 and 34 years old and in 45.5% of cases they had less than eight years of educational instruction. 57.2% never had a miscarriage, 63.3% had vaginal deliveries and 59.2% had full-term deliveries. Most women received prenatal care (95.9%). In 49.5% of cases, the diagnosis of maternal syphilis occurred during prenatal care. Only 67 (27%) of the pregnant women were treated properly and only 52 (29%) had their partners treated. The study shows a flaw in prenatal care with low effectiveness of the prevention actions, determining factors in the control of congenital syphilis.